An unexpected photoinduced cyclization to synthesize fully substituted γ-spirolactones via intramolecular hydrogen abstraction with allyl acrylates. Issue 9 (1st March 2022) - Sun, Xin; Zhou, Min; Zhu, Jing-Ping; Zhang, Xiang-Fei; Liu, Zu-Jiang; Li, Hao-Ran; Chen, Yan; Chen, He-Ping; Zhao, Jie; Pu, Jian-Xin; Yu, Miao; Liu, Ji-Kai; et al.
Abstract : A photoinduced intramolecular cyclization of allyl acrylates to synthesize fully substituted spiro-γ-butyrolactone compounds is described. The reaction is believed to proceed through an intramolecular hydrogen abstraction strategy. Abstract : A photoinduced intramolecular cyclization of allyl acrylates to synthesize fully substituted spiro-γ-butyrolactone compounds is described. The reaction is believed to proceed through activation of the carbonyl group upon ultraviolet irradiation, 1, 4-hydrogen atom transfer, and intramolecular cyclization of diradical species, an intramolecular hydrogen abstraction strategy, based on a series of control and isotope studies as well as DFT calculations.